(untitled) (Altre Modernità, 2012)
What exactly has the impact of globalized texts been on translation theory? How far has translation theory taken into account the countless new formats and new modalities? This paper sets out to identify points of contact between two different realms, namely, new media with its various forms of global texts on the one hand, and traductological considerations on the other. What will emerge from such a comparison will be a series of significant convergences as well as new openings towards global texts. This study will provide an overview of the work of McLuhan and the criticism of The Gutenberg Galaxy; Lefevere and the theory of systems applied to translation; Meschonnic and issues regarding rhythm and Skopostheorie and translation for the theatre. From the disintegration of the printed form, rather than a re-composition and new textual entities, this study will argue that new modalities have led to an increase in discursive elements and the need for a connection above the mere linguistic level.